2013
DOI: 10.1016/j.biopsych.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Shared and Distinct Intrinsic Functional Network Centrality in Autism and Attention-Deficit/Hyperactivity Disorder

Abstract: Background Individuals with autism spectrum disorders (ASD) often exhibit symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD). Across both disorders, observations of distributed functional abnormalities suggest aberrant large-scale brain network connectivity. Yet, common and distinct network correlates of ASD and ADHD remain unidentified. Here, we aimed to examine patterns of dysconnection in school-age children with ASD, ADHD and typically developing children (TDC) who completed a resting state fMRI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
267
4
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 316 publications
(299 citation statements)
references
References 103 publications
(147 reference statements)
21
267
4
7
Order By: Relevance
“…It is also consistent with evidence of enrichment for rare genetic variants that encode cell-adhesion and neuronal synapse scaffolding in both conditions (7). Although we did not find disease-specific fractional anisotropy alterations in ASD or ADHD in the present sample, two previous studies found differences between these disorders in terms of network topology (35,36). In contrast to the absence of significant differences between ADHD and ASD, we found differences in white matter structure in both the ASD group and the ADHD group, compared with the OCD group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is also consistent with evidence of enrichment for rare genetic variants that encode cell-adhesion and neuronal synapse scaffolding in both conditions (7). Although we did not find disease-specific fractional anisotropy alterations in ASD or ADHD in the present sample, two previous studies found differences between these disorders in terms of network topology (35,36). In contrast to the absence of significant differences between ADHD and ASD, we found differences in white matter structure in both the ASD group and the ADHD group, compared with the OCD group.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no fractional anisotropy differences were found in the ADHD group compared with the ASD group, and fractional anisotropy differences did not extend beyond the splenium in the OCD group compared with the control group. Our results in ADHD and ASD are consistent with two recent imaging studies that directly compared connectivity patterns in children and adolescents with ASD or ADHD and controls (35,36). These studies indicated that both ASD and ADHD are disorders involving large-scale connectivity impairments based on the diffuse nature of structural and functional connectivity differences found across the brain in each NDD compared with controls.…”
Section: Discussionsupporting
confidence: 91%
“…The DMN as the hallmark of resting state has been found altered in many neurological and psychiatric disorders, such as, among all, schizophrenia (Stephan et al, 2009;Woodward et al, 2011;Guo et al, 2014), mild cognitive impairment (Sinanaj et al, 2015) and ADHD (Sonuga-Barke and Castellanos, 2007;Castellanos et al, 2008;Fair et al, 2010;Tomasi and Volkow, 2012;Di Martino et al, 2013). Based on previous reports of abnormal laterality of the ADHD brain (Dennis and Thompson, 2013;Shang et al, 2013;Cao et al, 2014;Hale et al, 2014Hale et al, , 2015Keune et al, 2015;Silk et al, 2015), we could postulate that the asymmetric expression of neurodevelopmental genes might be at the origin of structural and functional changes in this disorder.…”
Section: Discussionmentioning
confidence: 92%
“…From a neuroimaging viewpoint, compelling evidence points to rather large-scale abnormalities in network organization in ADHD (Sergeant et al, 2006;Konrad and Eickhoff, 2010;Cao et al, 2013), affecting both functional (Cocchi et al, 2012;Colby et al, 2012;Fair et al, 2012;Tomasi and Volkow, 2012;Cao et al, 2013;Di Martino et al, 2013) and structural (Cao et al, 2013;Hong et al, 2014) connectivity. Moreover, an abnormal hemispheric asymmetry of brain structure and function was also consistently reported in ADHD (Dennis and Thompson, 2013;Shang et al, 2013;Cao et al, 2014;Hale et al, 2014Hale et al, , 2015Keune et al, 2015;Silk et al, 2015), suggesting a possible neurodevelopmental scenario for this disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation